Effectiveness of Local People's Perception on Ecotourism Participation in Bromo Tengger Semeru National Park, Indonesia - Purwanti, Rini (Jurnal Ilmiah Administrasi Publik, 2018)
Support of local people is important things regarding successful ecotourism management. Ranu Pani is located in Bromo Tengger Semeru National Park (BTSNP), Indonesia. This study aims was to examine how residents’ views and the relationship between perception, attitude, communication and participation on ecotourism. A questionnaire survey was conducted to get the data. For analyzing data, it used regression analysis through SPSS. The results showed that there was a relationship between positive perception, communication and participation. Most of respondents agreed ecotourism would like to improve attractiveness of the community, and raise incomes. Regarding communication, residents would like to give information and feel happy when visitors asking them about their nature and culture. Regarding attitude, most of respondents supported with national park management. However, they were only 58.7% satisfied with development of national park. Therefore, the authority should improve their capacity to provide more employment opportunities and to escalate residents-national park relationship.